2005
DOI: 10.2106/jbjs.d.02945
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of Femoral Rotational Alignment in Total Knee Arthroplasty

Abstract: All techniques resulted in highly variable rotational alignment, with no technique being superior. This variability was primarily due to the particular surgeon who was performing the alignment procedure. A navigation system that relies on directly digitizing the femoral epicondyles to establish an alignment axis did not provide a more reliable means of establishing femoral rotational alignment than traditional techniques did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(72 citation statements)
references
References 29 publications
(28 reference statements)
4
65
2
1
Order By: Relevance
“…Both systems attempt to use anatomic landmarks to define femoral component rotation, but intraoperative identification of landmarks such as the femoral epicondyles has been shown to have high interobserver variability. Siston et al compared the TEAs established by 11 orthopaedic surgeons to a reference axis established using a digitized model and found that fewer than 17% of the TEAs marked by the surgeons were rotated less than 5° from the reference axis [28]. Similarly, Yan reported interobserver variations of 4.2° for the TEA [29].…”
Section: Discussionmentioning
confidence: 99%
“…Both systems attempt to use anatomic landmarks to define femoral component rotation, but intraoperative identification of landmarks such as the femoral epicondyles has been shown to have high interobserver variability. Siston et al compared the TEAs established by 11 orthopaedic surgeons to a reference axis established using a digitized model and found that fewer than 17% of the TEAs marked by the surgeons were rotated less than 5° from the reference axis [28]. Similarly, Yan reported interobserver variations of 4.2° for the TEA [29].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst many opinions have been expressed in the literature as to which axes are the most reliable and/or show the least intra-/inter-observer variability, none seems to be superior [9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of anatomical landmarks have been proposed to achieve correct rotational alignment, such as the posterior condylar axis (PCA), surgical transepicondylar axis, clinical transepicondylar axis (CEA), and anteroposterior trochlear axis (i.e., Whiteside's anteroposterior axis) (3,4). The transepicondylar axis has been demonstrated, in theory, to be a reliable rotational reference line for properly placing the femoral component (5-7), but identifying it intraoperatively is difficult in some cases because of the low-profile geometry of and/or soft tissues covering the epicondyles (8,9). Therefore, surgeons typically estimate the transepicondylar axis from the PCA by using the twist angle determined on preoperative X-rays or computed tomography (CT) scans and set the cutting guide based on these measurements.…”
Section: Introductionmentioning
confidence: 99%